(3TQM bUjOI ddTeGNs - (3eLghds; (3GdTeGN Hf VQGQ Hf MQedI Hf SfGf GdeGRfj,J (B22 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe s)
(3ChdgG (B:s
(3CNHQfG jYbhH bGd GdCUeYi hCHh YHjOI gh GdTeGN hCSeg eYbd bGd GdCUeYi hChd gPg GdbUjOI (B:- (3YaG HWf ba ef SdjeGf aYGdf aPGJ GdaVGVG deTQaG GdfhGTQ s
(3BNQgG (B:s
(3hGdLeY CMbGa heQcO ehVY jQcO ajg Ci jKHJ ajg hESJhGg CYdGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B25s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdeLGejYs